Zinc, copper, and oxysterol levels in patients with type 1 and type 2 diabetes mellitus. Issue 6 (June 2020) - Samadi, Afshin; Isikhan, Selen Yilmaz; Tinkov, Alexey A.; Lay, Incilay; Doşa, Monica Daniela; Skalny, Anatoly V.; Skalnaya, Margarita G.; Chirumbolo, Salvatore; Bjørklund, Geir
Summary: Background: The present study has the objective to assess the zinc (Zn), copper (Cu), and oxysterols plasma levels in type 1 (DM1) (n = 26) and type 2 (DM2) (n = 80) diabetes patients, as compared to healthy controls (n = 71), in order to testify whether metal levels may have a significant impact on the association between oxysterols and diabetes. Methods: Plasma trace elements and plasma oxysterols were assessed using atomic absorption spectrometry and LC-MS/MS, respectively. Lifestyle, smoking status, alcohol intake, and drug usage, as well as microvascular complications, were also monitored and reported. Results: The obtained data demonstrated that both DM1 and DM2 patients were characterized by significantly elevated HbA1c, FBG, TC, LDL-C, VLDL-C, and TG levels as compared to controls. Plasma Zn levels and Zn/Cu ratio in DM1 and DM2 patients were about 3- and 2-fold lower than controls. No significant differences in plasma Cu levels were reported. The 7-ketocholesterol (7-kchol) levels in DM1 and DM2 patients exceeded these values in healthy individuals by 2.5 and 5-fold, respectively. Similarly, cholestan-3β, 5α, 6β-triol (chol-triol) levels were more than 3- and 6-fold higher when compared to the respective values in non-diabetic controls. In regression models decreased plasma Zn and elevated oxysterol levels were significantly associated with HbA1c and fasting plasma glucose levels, after adjustment for anthropometric and clinical variables, as well as routine biochemical markers. Conclusions: Plasma Zn concentration is inversely associated with both 7-kchol and chol-triol levels. Assessment of Zn and oxysterol levels may be used both for risk assessment and as targets for the treatment of diabetes mellitus. Highlights: Serum copper levels were not associated with diabetes development. Subjects with type 1 or type 2 diabetes showed diminished zinc levels in the serum. The zinc/copper ratio in diabetes subjects was 2-fold lower than healthy controls. Serum zinc levels were inversely correlated with circulating oxysterols.